Contribution of p53-dependent and -independent mechanisms to upregulation of p21 in Fanconi anemia. - Xavier Renaudin; Baraah Al Ahmad Nachar; Benedetta Mancini; Anna Gueiderikh; Noémie Louis-Joseph; Frédérique Maczkowiak-Chartois; Filippo Rosselli (PLoS Genetics)
Abnormal expression of the cell cycle inhibitor and p53 target CDKN1A/p21 has been associated with paradoxical outcomes, such as hyperproliferation in p53-deficient cancer cells or hypoproliferation that affects hematopoietic stem cell behavior, leading to bone marrow failure (BMF). Notably, p21 is known to be overexpressed in Fanconi anemia (FA), which is a rare syndrome that predisposes patients to BMF and cancer. However, why p21 is overexpressed in FA and how it contributes to the FA phenotype(s) are still poorly understood. Here, we revealed that while the upregulation of p21 is largely dependent on p53, it also depends on the transcription factor microphthalmia (MITF) as well as on its interaction with the nucleolar protein NPM1. Upregulation of p21 expression in FA cells leads to p21 accumulation in the chromatin fraction, p21 immunoprecipitation with PCNA, S-phase lengthening and genetic instability. p21 depletion in FA cells rescues the S-phase abnormalities and reduces their genetic instability. In addition, we observed that reactive oxygen species (ROS) accumulation, another key feature of FA cells, is required to trigger an increase in PCNA/chromatin-associated p21 and to impact replication progression. Therefore, we propose a mechanism by which p21 and ROS cooperate to induce replication abnormalities that fuel genetic instability.